A high-performance supercapacitor based on activated carbon fibers with an optimized pore structure and oxygen-containing functional groups. (14th December 2016) - Zhu, Kai; Wang, Yu; Tang, Joel A.; Guo, Shaohua; Gao, Zhongmin; Wei, Yingjin; Chen, Gang; Gao, Yu
Abstract : Activated carbon fibers with optimized pore structures and oxygen-containing functional groups display a remarkable capacitance and an excellent cycling performance. Abstract : Low-cost activated carbon fibers (ACFs) were prepared from polyacrylonitrile-based precursor fibers abandoned by local factories via carbonization and CO2 activation. Oxygen-containing functional groups were introduced on the ACF surface via nitric acid and thermal treatment. ACFs with optimized pore structures and oxygen-containing functional groups display a remarkable capacitance of 214 F g −1 at a current density of 0.5 mA cm −2 and present an excellent cycling performance with a capacity retention of almost 100% over 3000 cycles. Moreover, the rate capability gains a significant improvement due to the existence of functional groups. The superb electrochemical performance of these materials provides a template of how to better engineer the ACFs' pore architecture and surface modifications to design enhanced electrode materials for high-performance supercapacitors.